2021
DOI: 10.3390/ijms22126365
|View full text |Cite
|
Sign up to set email alerts
|

Factors Involved in Morphogenesis in the Muscle–Tendon–Bone Complex

Abstract: A decline in the body’s motor functions has been linked to decreased muscle mass and function in the oral cavity and throat; however, aging of the junctions of the muscles and bones has also been identified as an associated factor. Basic and clinical studies on the muscles, tendons and bones, each considered independently, have been published. In recent years, however, research has focused on muscle attachment as the muscle–tendon–bone complex from various perspectives, and there is a growing body of knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…To discuss the morphogenesis, one must also consider the theory called as the “muscle–tendon-bone complex 53 ” which has been reported recently. According to this theory, differences in the function and load of the muscle attached to the bone could drive the morphogenesis and maintenance of the bone itself.…”
Section: Discussionmentioning
confidence: 99%
“…To discuss the morphogenesis, one must also consider the theory called as the “muscle–tendon-bone complex 53 ” which has been reported recently. According to this theory, differences in the function and load of the muscle attached to the bone could drive the morphogenesis and maintenance of the bone itself.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, since it is known that regenerated muscles are formed inside the tissue immediately after the necrosis of muscle, the plasticity of the muscle has been investigated from various viewpoints [ 82 , 83 , 84 , 85 ]. Recent studies have also revealed that myotendinous junctions, connecting tendon tissues, and bones develop and regenerate as tissue complexes, particularly in muscle attachments, such as the temporomandibular region [ 86 ]. Musculoskeletal disorders in elderly people are attributable to the destruction of the muscle–bone connections as well as age-related changes in muscles, and further studies in this area are required.…”
Section: Discussionmentioning
confidence: 99%
“…Tnmd was also detected at the mRNA level. Although Sox9 is known to be a marker of cartilage and bone development, in recent years it has also been reported to be a marker common to the “muscle–tendon–bone complex” at muscle attachment sites [ 35 , 36 , 37 , 38 , 39 ]. A paper examining the origin of the extraocular muscles that move the eyeball shows that several muscles originate from common tendons for their complex functions [ 40 ].…”
Section: Discussionmentioning
confidence: 99%